2021
DOI: 10.3389/fonc.2020.601620
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Carbon Ion Radiation Induces Bystander Effect on Metastasis of A549 Cells and Metabonomic Correlation Analysis

Abstract: ObjectiveTo analyze the effect of carbon ion (12C6+) radiation may induce bystander effect on A549 cell metastasis and metabonomics.MethodsA549 cell was irradiated with carbon ion to establish the clone survival model and the transwell matrix assay was applied to measure the effect of carbon ion on cell viability, migration, and invasion, respectively. Normal human embryonic lung fibroblasts (WI-38) were irradiated with carbon ions of 0 and 2 Gy and then transferred to A549 cell co-culture medium for 24 h. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Purine metabolites were increased in RTresistant cell lines when DNA damage occurred (52) after photon irradiation and the inhibition of de novo purine synthesis impairs DNA reparation (53) after irradiation. Alternation of purine metabolism could also be observed after carbon ion irradiation (54). In our research, several metabolites in purine metabolism were significantly discriminative between the two groups.…”
Section: Discussionsupporting
confidence: 59%
“…Purine metabolites were increased in RTresistant cell lines when DNA damage occurred (52) after photon irradiation and the inhibition of de novo purine synthesis impairs DNA reparation (53) after irradiation. Alternation of purine metabolism could also be observed after carbon ion irradiation (54). In our research, several metabolites in purine metabolism were significantly discriminative between the two groups.…”
Section: Discussionsupporting
confidence: 59%
“…As shown in Fig. 3B, these changed genes induced by carbon-ion irradiation were enriched in the p53 signaling pathway and metabolism-related pathways, which correlate with carbon-ion-induced radiation sensitivity ( 38 , 39 ). These findings suggest that the biological effects induced by carbon-ion irradiation of different LET are closely correlated with chromatin accessibility and gene transcription.…”
Section: Resultsmentioning
confidence: 86%
“…The interaction between CDK1 and p53 has been studied ( 54 ), but our data are able to explain from a chromatin accessibility perspective how carbon ions alter CDK1 transcript levels and influence the p53 signaling pathway. In addition, metabolomic analysis revealed that differential metabolites were enriched in the purine metabolic pathway 24 h after carbon-ion irradiation ( 39 ). We also found that genes regulated by chromatin accessibility were enriched in purine metabolism after irradiation with 50 keV/µm carbon ions, which was consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…It could be the bystander effect of radiotherapy, that is, the same effect of radiotherapy on cells, tissues or organs in non-irradiated areas ( Wang et al, 2015 ; Fu et al, 2020 ). After irradiation, cells in the irradiated area can secrete cytokines, small molecular metabolites, exosomes or microvesicles containing various substances, and other media ( Lin et al, 2017 ; Ariyoshi et al, 2019 ; Ni et al, 2020 ; Mukherjee et al, 2021 ), resulting in metabolic disorders, apoptosis, endoplasmic reticulum and golgi dysfunction of cells in non-irradiated areas ( Yakovlev, 2015 ; Jella et al, 2018 ; Mladenov et al, 2018 ; Dong et al, 2020 ; Heeran et al, 2021 ; Yang et al, 2021 ). Earlier studies reported elevated levels of CRP in circulating blood, and splenic cells exhibited enhanced levels of oxidative stress and increased apoptosis after cranial irradiation in rats ( El-Din et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%